Evaluasi Geometri Jalan Angkut Komatsu HD785-7 Dari PNBP 4 Ke Crusher 6 Tambang Batu Kapur PT. Semen Padang. - Ryan Markah; Raimon Kopa; Tri Gamela Saldy; Rudy Anarta (Departemen Teknik Pertambangan FT UNP, 2022)
Every mining activity always requires a haul road to move the minerals to be produced. PT. Semen Padang is an open-pit mining company that produces limestone or limestone as a cement making material. One of the mining activities that can affect the production target is the transportation process. From the results of observations about the geometry of the PNBP 4 to Crusher 6 haul roads, several non-ideal road geometries were found that could affect the production achievement. The non-ideal condition of the haul road geometry found is, the condition of the straight road is 18.9 meters wide, while the ideal is 18,025 meters. Then the corner with a width of 22.8 meters, while ideally 26,154 meters. Then the road slope is found to be 21.8%, while ideally it is 10-12%. The condition of some of these road geometry factors affect the cycle time of the material transport process. Where the condition of hauling the contents along the haul road takes 7 minutes 48 seconds. While the condition of empty hauling takes 5 minutes 23 seconds. In the comparison of actual field data with grade calculation results, it was found that there were still road grades that were not ideal, namely in the segment 25-27. Then to achieve the ideal cross slope value of 2%, then the height difference between the left and right roads to the haul road axis that must be made is 18 cm. Based on the results of the evaluation of the haul road geometry from PNBP 4 to Crusher 6, it can be concluded that there are actual road conditions that are not in accordance with the ideal calculation standard. Therefore, it is necessary to increase the width on the straight condition road and increase the width on the bend condition road. In the superelevation section, the height difference that must be made between the inside and outside of the haul road bend is 1,02 meters. Then to overcome the runoff water that inundates the haul road during rainy weather, it is necessary to make several drainage channels.